2015
DOI: 10.1523/jneurosci.0099-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Differential Muscarinic Modulation in the Olfactory Bulb

Abstract: Neuromodulation of olfactory circuits by acetylcholine (ACh) plays an important role in odor discrimination and learning. Early processing of chemosensory signals occurs in two functionally and anatomically distinct regions, the main and accessory olfactory bulbs (MOB and AOB), which receive extensive cholinergic input from the basal forebrain. Here, we explore the regulation of AOB and MOB circuits by ACh, and how cholinergic modulation influences olfactory-mediated behaviors in mice. Surprisingly, despite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
106
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(116 citation statements)
references
References 81 publications
10
106
0
Order By: Relevance
“…GCs are a heterogeneous group of neurons, and they exhibit distinct characteristics in the AOB and MOB, including synaptic properties and regulation by neuromodulatory transmitters (Castro et al, 2007; Zimnik et al, 2013; Burton and Urban, 2015; Smith et al, 2015). Accordingly, we found that the voltage sensitivity of I h was modulated by cAMP in the MOB, but not in the AOB; nevertheless, I h activation was faster in the AOB in the presence of cAMP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GCs are a heterogeneous group of neurons, and they exhibit distinct characteristics in the AOB and MOB, including synaptic properties and regulation by neuromodulatory transmitters (Castro et al, 2007; Zimnik et al, 2013; Burton and Urban, 2015; Smith et al, 2015). Accordingly, we found that the voltage sensitivity of I h was modulated by cAMP in the MOB, but not in the AOB; nevertheless, I h activation was faster in the AOB in the presence of cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed in OB slices using methods previously described (Smith et al, 2015). Briefly, brain slices were prepared in an oxygenated ice-cold artificial CSF (ACSF) containing low Ca 2+ (0.5 m m ) and high Mg 2+ (6 m m ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the MOB and suggests that these circuits utilize different physiological solutions for processing odour information (Smith et al . ). While there is strong structural and biophysical characterization of the role of serotonergic signalling in the MOB (Hardy et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the OB, Ach has been shown to modulate principal cells and different classes of interneurons via both nicotinic and muscarinic receptors (Ravel et al, 1990; Castillo et al, 1999; Crespo et al, 2000; Pressler et al, 2007; D'souza and Vijayaraghavan, 2012; Ma and Luo, 2012; D'souza et al, 2013; Rothermel et al, 2014; Liu et al, 2015; Smith et al, 2015; Bendahmane et al, 2016). From these data, the net functional effect of ACh inputs to the OB can be constructed as enhancing mitral cell selectivity to odorants through increased inhibition and filtering of low amplitude inputs in concert with increased excitability in response to selective odorants; this idea is supported by behavioral and electrophysiological data (Elaagouby et al, 1991; Linster et al, 2001; Wilson et al, 2004; Mandairon et al, 2006; Devore et al, 2014).…”
Section: Introductionmentioning
confidence: 99%